Formulasi Sabun Cair Perak Nanopartikel dengan Penstabil Polyvinil Alcohol : Sabun Cair Perak Nanopartikel - Sutriyo; Hanandi, Sharon; Putri, Kurnia Sari Setio; Poetri, Okti Nadia; Annisa, Syifa; Rahmasari, Ratika (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
According to Global Burden of Disease reported on 2019, about 1.53 million deaths caused by infectious diseases such as pneumonia and diarrhea. Triclosan is one of the active ingredient commonly used in antibacterial soap as one way to prevent the spread of infectious disease.. However, bacteria resistance against triclosan has been reported. Silver nanoparticles (AgNP) is an alternative antibacterial that potential to be used in liquid hand wash. However AgNp tend to aggregate during storage, thus stabilizer is needed This study aims to synthesize AgNP, formulate the liquid hand wash contain AgNP with polyvinil alcohol as stabilizer, and evaluate its effectiveness against Escherichia coli, Staphylococcus aureus, and Salmonella thypi. AgNP was prepared using the chemical reduction method between silver nitrate and sodium borohydride, followed by its characterization using UV-Vis spectrophotometer, TEM, PSA, and AAS. The physical characteristic of AgNp-liquid hand wash were also evaluated. Further, the antibacterial activity of AgNP-handwash was evaluated by phenol coefficient method. The peak of UV absorption spectrum of colloidal was found at 404.2 nm indicated the presence of AgNP. Ag content in AgNP colloidal was 38.405 mg/Kg ± 0,008. The spherical shape of AgNP was observed. The AgNP size was 65.1 nm with polydispersity index value of 0.543, and zeta potential value was -22.25 mV. The obtained AgNP-hand wash met the Indonesian standard criteria and was stable for 28 days. The best phenol coefficient value was obtained at formulation with addition of 30% AgNP (0.1 for S. typhi, 0.4 for E. coli, and 0.01 for S. aureus).